The COX2 genetic variants in oral squamous cell carcinoma in Turkish population - Cacina, Canan; Kaşarci, Göksu; Bektaş, Kivanç; Unur, Meral; Cakmakoglu, Bedia (Cellular and Molecular Biology, 2018)
Oral squamous cell carcinoma (OSCC) is a common type of cancer that genetic and environmental factors also lifestyle habits, infections play important roles in the pathogenesis of disease. Cyclooxygenase 2 (COX2) is the inducible isoform of enzyme which convert arachidonic acid to prostaglandins. It was known that alterations in COX2 gene functions contribute to the inflammation process thus induce cancer progression, including cell proliferation, apoptosis, adhesion, invasion and metastasis. A total of 114 cases 165 healthy individuals were included in present study. We aimed to evaluate possible association between the COX2; -765, -1195 polymorphisms and the risk of OSCC. The genotypes were determined by using polymerase chain reaction restriction fragment length polymorphism techniques. In our study group the carriers of COX2 -765 C allele were statistically higher in patients compared with controls and individuals who had CC genotype had a 3,4 fold high risk for OSCC (p <0,05). We also observed the COX2 -1195 AA genotype frequency was higher in cases that of healthy group and individuals who had AA genotype showed a 1,7 fold increased risk for OSCC (p < 0,05). Haplotype analysis confirmed our result and revealed that the frequencies of COX2 -765C, -1195A haplotype frequencies were significantly higher in patients as compared with those of controls. In conclusion we suggest that COX2, -765, -1195 polymorphisms appear to be an important predictive factor and may be a prognostic biomarker for risk of OSCC. Further investigations with larger study groups are needed to fully elucidate the role of COX2 -765, -1195 variations in the development of OSCC.